Polymorphisms and Associations of the NRAMP-1 and iNOS Genes on Newcastle Disease and Salmonella enteritidis Resistances in SenSi-1 Agrinak Chickens - Ardiyana, M.; Gunawan, A.; Murtini, S.; Sartika, T.; Sumantri, C. (Tropical Animal Science Journal, 2020)
NRAMP-1 and iNOS genes were reported to be associated with a defense mechanism against bacteria and virus infections. This study aimed to identify NRAMP-1 and iNOS genes polymorphisms and their associations with the defense mechanisms against Salmonella enteritidis and Newcastle Disease (ND) in SenSi-1 Agrinak chicken. The present study used a total number of 172 SenSi-1 Agrinak chicken. Identifications of NRAMP-1 and iNOS genes polymorphisms were performed by PCR-RFLP method. NRAMP-1 and iNOS genotypes were associated with immunoglobulin Y (IgY) concentration, specific antibodies against S. enteritidis and ND using General Linear Model (GLM). Immunity characteristics were further grouped into high, medium, and low categories. NRAMP-1|SacI exon 11 and iNOS|AluI intron 24 in SenSi-1 Agrinak chickens were polymorphic. TC genotype has a higher immune response to infectious agents compared to TT and CC genotypes. The frequency of C allele was higher than the T allele in the concentration of immunoglobulin Y (IgY), antibodies titers against S enteritidis and ND. The TC genotype of NRAMP-1 gene was significantly associated with ND antibody titers, and the TT genotype of iNOS was significantly associated with S. enteritidis specific antibody. NRAMP-1 and iNOS genes can be used as potential candidate genes for immune traits in SenSi-1 Agrinak chickens.